Gastrointestinal Symptoms and Liver Dysfunction in Children with Covid 19 Infection (Bangladesh Journal of Child Health, 2024)
Background: Although, the primary organ of involvement are lungs in Coronavirus disease 2019 (COVID-19), however liver, and gastrointestinal (GI) involvement is being increasingly reported in the emerging data from various centers across the world. Objective: To observe the gastrointestinal symptoms and liver dysfunctions in children with Covid 19 infection. Methods: This retrospective observational study was conducted in children with Covid 19 RT PCR positive, aged between 0 and 15 years admitted from March 2020 to March 2022. Data of 103 consecutive children were collected retrospectively. We analyzed the clinical and laboratory data of 101 children after exclusion 2 children as associated acute HAV infection and liver cirrhosis using Statistical Package for Social Science (SPSS) for Windows version 29. Results: A total of 101 children with Covid 19 were analyzed in this study. Of these 101 children, 61 were male. The mean age was 5.4 years (SD 4.9). 44 children had gastrointestinal presentation in the form of vomiting, diarrhea, abdominal pain. Most common gastrointestinal presentation were nausea and vomiting (34.7%), then diarrhea (21.8%), abdominal pain (15.8%), hepatosplenomegaly (3%), ascites and jaundice 1% in each respectively. Total 17(16.8%) patients presented with gastrointestinal manifestations without any respiratory symptoms or any other coinfections including 10 acute gastroenteritis, 4 acute gastritis, 2 dysenteries (bloody stool) with stool culture negative and 1 intussusception. Liver dysfunctions were found in 16(15.8%) patients in the form of raised ALT (16) or AST (4) or low albumin (10). All 10 children with low albumin had MIS-C. None of them developed liver failure. There was statistically no significant difference between covid 19 children with GI symptoms and without GI symptoms clinically and biochemically except longer hospital stays more frequent in GI symptoms group (p=0.03). Conclusion: Gastrointestinal symptoms may be a presenting clinical feature even without any respiratory symptoms in Covid 19 children. Liver dysfunction is uncommon in children with mild Covid 19 infections. If liver dysfunction is found, we think that it may progress to more severe infection like MIS-C or associated with co infection.Bangladesh J Child Health 2023; Vol 47 (2) : 84-88